THE ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF REGIONAL GOVERNMENT APPARATUSES OF BANDA ACEH - Yunina, Fitri; Lastri, Surna; Agustina, Maya; Yani, Friska (J-ISCAN: Journal of Islamic Accounting Research, 2024)
The phenomenon that occurred in 2017 based on the BPK's Opinion on the Financial Report of the Banda Aceh City Government was Fair Without Exception or "Reasonable Without Exception", however, the BPK found that there were weaknesses in the internal control system in the preparation of the Banda Aceh City Government's financial reports, including: inventory management is not yet fully adequate; management of fixed assets is not yet fully capable; and the management of grants and social assistance is not yet fully capable. The aim of this research is to analyze the factors that influence the performance of Banda Aceh City Regional Work Units. This research is causative associative quantitative research. The data collection technique uses questionnaire data by distributing questionnaires to Banda Aceh City the performance of regional apparatuses with a population of 92 employees in the Goods/Services Management and Accounting Sectors. Testing was carried out using multiple linear regression analysis methods. The results of the research show that understanding the regional financial accounting system, regional financial administration and management of regional property have an influence both simultaneously and partially on the performance of regional apparatuses of Banda Aceh.